Nutrition Knowledge of Elderly and Middle-age Urban Population and Its Effects on Diet Quality and Dairy Consumption: A Cross-sectional Study in Eight Cities of China (P10-060-19). (13th June 2019) - Wang, Yan; Meng, Liping; Feng, Haotian; Li, Ting
Abstract: Objectives: The main aim of the present study was to investigate the nutrition knowledge and diary knowledge of elderly and middle-aged urban community-dwelling population, and their effects on diet quality and dairy consumption. Methods: Data shown in present study was extracted from a cross-sectional survey, the Chinese Urban Adults Diet and Health Study, conducted in eight cities from March to July, 2016. Data were collected from subjects by trained interviewers using an interviewer-administered questionnaire in two parts related to social-demographic factors and knowledge, attitude, and practice (KAP). For knowledge, seven questions and six questions were used to measure subjects' knowledge towards nutrition and the health benefits of dairy products, respectively. One-time 24-h dietary recall and the semi-quantitative Food Frequency Questionnaire (semi-FFQ) for one recent month were used to investigate the food consumption with the help of a standard reference picture book, bowls, plates, and spoons. China Healthy Diet Index (CHDI) and Dietary Diversity Scores (DDS) were used to measure dietary quality. Covariates were determined by questionnaires and interviews. Results: A total of 1090 individuals aged 62.12 ± 8.62 (range 45–81 years) were included, 60.8% were female. Males, subjects with lower household monthly income and lower education level had significantly lower knowledge scores. Participants with better nutrition knowledge had significantly higher CHDI score (63 vs 54, P  < 0.05) and DDS score (6.3 vs 5.7, P  < 0.05) when compared to subjects with poor nutrition knowledge. The multivariate logistic regression model in Table 1 illustrated that, after adjusting for age, gender, education level, household income and lactose intolerance symptoms, a significantly increased rate of no dairy consumption was observed among participants with poor nutrition knowledge (OR = 2.5; 95%:1.4 to 4.2) and participants with poor dairy knowledge (OR = 3.1; 95%:1.5 to 6.5). Conclusions: The findings of this study indicated that knowledge gaps surrounding nutrition and dairy products exist in Chinese elderly and middle-age urban population. Moreover, good command of nutrition knowledge and dairy knowledge has a positive effect of dietary quality and milk consumption rate. Funding Sources: This study was funded by Inner Mongolia Yili Industrial Group Co., Ltd. Supporting Tables, Images and/or Graphs: